2008
DOI: 10.1177/0363546507312165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy and Eccentric Exercises in the Treatment of Recreational Athletes with Chronic Achilles Tendinopathy

Abstract: Low-level laser therapy, with the parameters used in this study, accelerates clinical recovery from chronic Achilles tendinopathy when added to an EE regimen. For the LLLT group, the results at 4 weeks were similar to the placebo LLLT group results after 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 46 publications
5
131
0
5
Order By: Relevance
“…Improvements in the intervention group were also noted in secondary measures, including tenderness to palpation, crepitation, morning stiffness, and active dorsiflexion range of motion. 127 An additional study in 7 patients with bilateral Achilles tendinopathy yielded positive results when examining the influence of LLLT. 12 Using a 904-nm probe, at 5.4 J per point, Bjordal and colleagues, 12 identified that LLLT can reduce pain and inflammation associated with an acute (exercise induced) exacerbation of Achilles tendonitis.…”
Section: Laser Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Improvements in the intervention group were also noted in secondary measures, including tenderness to palpation, crepitation, morning stiffness, and active dorsiflexion range of motion. 127 An additional study in 7 patients with bilateral Achilles tendinopathy yielded positive results when examining the influence of LLLT. 12 Using a 904-nm probe, at 5.4 J per point, Bjordal and colleagues, 12 identified that LLLT can reduce pain and inflammation associated with an acute (exercise induced) exacerbation of Achilles tendonitis.…”
Section: Laser Therapymentioning
confidence: 98%
“…130 Few studies, however, have overtly examined the influence of LLLT in human subjects with Achilles tendinopathy. 12,127 LLLT enhanced outcomes in a group of 20 subjects (12 male, 8 female), when coupled with eccentric exercises, compared to 20 subjects (13 male, 7 female) in an eccentric exercise group who received placebo laser treatment. 127 There were no statistical differences in age, height, weight, symptom duration, or quantity of active ankle dorsiflexion between the randomly assigned groups.…”
Section: Laser Therapymentioning
confidence: 99%
“…Five relevant studies [3][4][5][6][7] were located and categorized as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2011).…”
Section: Results Of Searchmentioning
confidence: 99%
“…Tendinopathies are clinically relevant to athletic trainers and sports-medicine rehabilitation experts. The potential benefits of managing pain associated with tendinopathy have been investigated using low-level laser therapy (LLLT) [3][4][5][6][7] and are still somewhat inconclusive. Further exploration, however, into the clinical effectiveness of using LLLT is warranted.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…Vários estudos, tanto em cultura de células como em 38 animais e humanos têm sido feitos de forma a avaliar os possíveis efeitos desta energia (177,(196)(197)(198)(199)(200) .…”
Section: Lllt Em Cultura De Célulasunclassified